Contrasting distributions of glycerol dialkyl glycerol tetraethers (GDGTs) in speleothems and associated soils - Blyth, Alison; Jex, Catherine; Baker, Andy; Khan, Stuart; Schouten, Stefan (Pergamon, 2014)
Glycerol dialkyl glycerol tetraethers (GDGTs) preserved in speleothems can form useful records of terrestrial palaeotemperature. However, understanding of the sources of these compounds in caves is limited, particularly whether or not they should be considered as an in situ signal derived from microbial communities in the cave or vadose zone, a transported soil signal, or a mixture of the two. We have analysed speleothem samples and related soils from five cave sites and demonstrate that clear differences were apparent between soils and speleothems in GDGT distributions. Speleothems were primarily, but not uniformly, dominated by crenarchaeol, reflected in the branched and isoprenoid tetraether (BIT) index values, and had a lower relative abundance of the crenarchaeol regioisomer than soils. The most distinct differences were in the bacterially derived branched GDGTs, where no relationship was seen between speleothems and soils for the cyclisation of branched tetraethers (CBT) index, with speleothems in four out of five caves showing a greater degree of cyclisation in GDGT structures than could be explained by measured pH values. Differences in speleothem GDGT composition between sites were also seen. We suggest that the speleothem GDGT record is distinct from the GDGT distribution produced in soils, and is primarily derived from in situ microbial communities within the cave or vadose zone. Variation within these communities or in the cave microenvironment also acts to produce site-specific differences.